Analysis of the Role of Experiential Marketing and Social Influence on Students Purchase Intention towards Local Fashion Brand - Sari, Dinny Talita; Izaak, Wilma Cordelia (Universitas Muhammadiyah Pontianak, 2025)
The local fashion industry is currently experiencing rapid growth, particularly among the younger generation, especially students. This study aims to analyze the impact of Experiential Marketing and Social Influence on the purchase intention of local fashion brands among students in East Java. A quantitative approach with data analysis using SEM PLS and data collection through an online questionnaire was employed. The results of the study indicate that Experiential Marketing has a positive impact on purchase intentionion. Additionally, Social Influence also proved to have a positive impact on purchase intentionion. Based on these findings, it is recommended that local fashion brands strengthen interactions with their audience on social media and leverage social influence through influencers and word-of- mouth program.